Thrombosis and Dissection of the Abdominal Arteries Associated with Infarcts of Solid Organs in a Patient with COVID-19: A Novel Clinical Entity - Voci, Davide; Micieli, Evy; Johner, Fabian A.; Kucher, Nils; Barco, Stefano (Hämostaseologie, 2021)
The clinical spectrum of patients with coronavirus disease 2019 (COVID-19) ranges from asymptomatic cases to severe pneumonia with acute respiratory distress syndrome. COVID-19 is associated with an increased risk of thromboembolic complications, notably pulmonary embolism and deep vein thrombosis. Arterial cardiovascular complications and myocarditis have also been described in association with COVID-19, but appear to be less prevalent. In this report of a 57-year-old man with multiple splanchnic infarctions, arterial dissections and COVID-19 as the sole potential trigger, we describe a novel type of complications and put it in the context of a growing literature on this topic.
Keywords: COVID-19; thrombosis; anticoagulation; dissection; splanchnic infarction; splanchnic thrombosis